DESIGN OF MIXTURE FINE GRAIN CONCRETE - Askarov Bakhtiyor Askarovich; Sobirova Mukaddas Khamidullaeva. (Scholar Express Journal, 2021)
The actual connection of the application of fine-grained concrete to the production of bored piles with the urban program for the renovation of the central districts of the city is given, information is provided on the methodology for designing a fine-grained concrete composition for the construction of bored piles; describes the problem of manufacturing finegrained concrete directly on the construction site and a proposal for its solution; the substantiation of application of fine-grained concrete mixes is given; it is indicated the possibility of achieving a better composite with careful control of the creation of its matrix at all levels, the factors affecting each level of hardening of the concrete mixture and the characteristics of the composite are listed
Keywords: Fine-grained concrete; application; composition; characteristics